Hydrides of Cu and Mg Intermetallic Systems: Characterization, Catalytic Function and Applications in Neutron Diffraction - M. H. Braga (2012)
The worldwide demand for energy in the 21st century is growing at an alarming rate. The European World Energy Technology and Climate Policy Outlook [WETO] predicts an average growth rate of 1.8% per annum for the period 2000-2030 for the world energy demand (European Commission, 2003). The increased demand is being met largely by reserves of fossil fuel that emit both greenhouse gases and other pollutants. Since the rate of fossil fuel consumption is higher than the rate of fossil fuel production by nature, these reserves are diminishing and they will become increasingly expensive. Against this background, the transition towards a sustainable, carbon-free and reliable energy system capable of meeting the increasing energy demands becomes imperative. Renewable energy resources, such as wind, solar, water, wave or geothermal, can offer clean alternatives to fossil fuels. Despite of their obvious advantages renewable energy sources have also some drawbacks in their use because they are unevenly distributed both over time and geographically. Most countries will need to integrate several different energy sources and an advanced energy storage system needs to be developed.